Is Prevention of Suicide Worth Less? -A Comparison of the Value per Statistical Life - Elin Vimefall; Mattias Persson; Sara Olofsson; Lars Hultkrantz (Örebro University School of Business, 2019)
This paper compares the value per statistical life (VSL) in the context of suicide prevention to that of prevention of traffic fatalities. We conducted a contingent valuation survey with questions on willingness to pay (WTP) in both contexts by administering a web questionnaire to 1038 individuals aged 18 to 80. We conjectured that WTP for a given impact on the number of fatalities would be lower for suicide prevention because suicide, at least to some degree, is the result of individuals' own decisions. However, this hypothesis was not supported by the within- or between-sample estimates of VSL or by responses to direct questions. Hence, no support is provided for the use of a lower valuation of the impact of suicide prevention than for risk-reducing programs in other fields, such as traffic safety.
Keywords: D61; I18; J17; 330; Value of statistical life; Willingness to pay; Mental health; Cost-benefit; Altruism